The The Correlation Between Human Immunodeficiency Virus (HIV) Infections in Pregnancy and Low Birth Weight Infants - Muhammad Ali Shodikin; Inke Kusumastuti; Wahidah Nur Indasyah (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: The prevalence of Human Immunodeficiency Virus (HIV) infection in pregnancy were increase in developing countries. The existence of infection interferes with the absorption of nutrients due to accumulation of inflammatory cells in the placenta can cause the infant born with low birth weight. Objective: The purpose of this study was to determine the correlation of HIV infections in pregnancy and low birth weight infant. Methods: This research used an observational analytic design with a retrospective approach. The samples were positive and negative HIV mother with their infants that hospitalized at dr. Soebandi Hospital, Jember, from August 2014 - July 2017. The data were analysed by Fisher's Exact. Results: This study was found 52 positive HIV mother with their infants and 52 negative HIV mother with their infants. Nine from 52 infants (17.3%) who born from positive HIV mother were low birth weight. Only 3 from 52 infants (5.8%) who born from negative HIV mother were low birth weight. Data analysis using Fisher’s Exact was obtained p value = 0.06. Conclusion: There was no significant correlation of HIV infections in pregnancy and low birth weight infant.